2003
DOI: 10.1007/s00330-002-1588-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of helical CT with angiography in pulmonary embolism: global and selective vascular territory analysis. Interobserver agreement

Abstract: The objective of this prospective study was to evaluate the sensitivity, specificity, positive and negative predictive values, and interobserver agreement in the diagnosis of pulmonary embolism with helical CT, compared with pulmonary angiography, for both global results and for selective vascular territories. Helical CT and pulmonary angiography were performed on 66 consecutive patients with clinical suspicion of pulmonary embolism. The exams were blindly interpreted by a vascular radiologist and by two indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…While the clinical performance of 64 Cu-FBP8-PET remains to be demonstrated, the high thrombus uptake observed in this study for both PE and DVT suggests the potential of this molecular imaging approach using PET. The high target:background contrast may allow imaging of emboli in the distal branches of the pulmonary circulation, detected with lower sensitivity by CT angiography (3). Moreover, 64 Cu-FBP8-PET may provide an alternative to contrast-enhanced CT for detection of PE in renally-insufficient patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the clinical performance of 64 Cu-FBP8-PET remains to be demonstrated, the high thrombus uptake observed in this study for both PE and DVT suggests the potential of this molecular imaging approach using PET. The high target:background contrast may allow imaging of emboli in the distal branches of the pulmonary circulation, detected with lower sensitivity by CT angiography (3). Moreover, 64 Cu-FBP8-PET may provide an alternative to contrast-enhanced CT for detection of PE in renally-insufficient patients.…”
Section: Discussionmentioning
confidence: 99%
“…While contrast-enhanced computed tomography (CT) has become the gold standard for PE (1, 2), its sensitivity decreases as the location of the PE becomes more distal (3). Furthermore, contrast-enhanced CT is contraindicated in patients with poor renal function owing to the risk of contrast-induced nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Practical advantages of spiral CT include ready availability, minimally invasive, rapid, cost-effective availability for follow up and same frequency of technically inadequate examination as catheter angiography, which is approximately 5%. 23,24 Spiral CT pulmonary angiography (CTPA) is a routine 24-h/day technique. The CT scan is more readily accessible than a nuclear medicine study and obviates the complications that occur by heart catheterization in catheter angiography in high-risk patients.…”
Section: D-dimer Blood Testmentioning
confidence: 99%
“…The incidence of indeterminate studies is reported to be between 0.5 and 10.8% with a mean of 6.4%. 5,[24][25][26][27][28][29][30][31][32] The two most common causes are respiratory motion and poor contrast enhancement. 24…”
Section: Indeterminate Mdct-pa Studymentioning
confidence: 99%